2020
DOI: 10.1155/2020/4051474
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide/TEMPO-Nanocellulose Nanohybrid-Based Electrochemical Biosensor for the Determination ofMycobacterium tuberculosis

Abstract: A novel peptide nuclide acid (PNA) electrochemical biosensor based on reduced graphene oxide (NH2-rGO)/2,2,6,6-tetramethylpiperidin-1-yl)oxyl nanocrystalline cellulose (TEMPO-NCC) for the detection of Mycobacterium tuberculosis (M. Tuberculosis) is described. In this study, the nanohybrid films NH2-rGO/TEMPO-NCC were immobilized onto screen-printed carbon electrode (SPE) via a simple drop-coating method. The electrochemical characterization of the designed electrode was investigated using cyclic voltammetry (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…The results from CV demonstrate that CTAB was able to provide conductive properties to NCC in order to accelerate the electron transfer on the electrode surface. As previously reported, the introduction of the CTAB surfactant has increased the dispersion of cellulose nanocrystals (CNCs) and the dispersive effect of nanoparticles increases the conductive probability [27,37]. The results also show that the electroactive surface area of SPCE/MPA-Fe 3 O 4 /NCC/CTAB was increased by approximately 54.5% compared to the bare SPCE.…”
Section: Electrochemical Characterizationsupporting
confidence: 79%
See 2 more Smart Citations
“…The results from CV demonstrate that CTAB was able to provide conductive properties to NCC in order to accelerate the electron transfer on the electrode surface. As previously reported, the introduction of the CTAB surfactant has increased the dispersion of cellulose nanocrystals (CNCs) and the dispersive effect of nanoparticles increases the conductive probability [27,37]. The results also show that the electroactive surface area of SPCE/MPA-Fe 3 O 4 /NCC/CTAB was increased by approximately 54.5% compared to the bare SPCE.…”
Section: Electrochemical Characterizationsupporting
confidence: 79%
“…This increment shows the ability of the developed electrochemical for providing a wide area platform [32] for DNA immobilization; thus, it can influence the sensitivity of detection [18,38]. Furthermore, the linearity of the plots has suggested that the electron transfer occurred was due to the diffusion-controlled electron transfer process [27,39].…”
Section: Electrochemical Characterizationmentioning
confidence: 87%
See 1 more Smart Citation
“…Recently, they modified the above PNA-GO biosensor for more sensitive detection of M. Tuberculosis DNA by replacing NH 2 -GO/QDs nanocomposites with amine-functionalized reduced graphene oxide (NH 2 -rGO) and 2,2,6,6-tetramethylpiperidin-1-yl) oxyl nanocrystalline cellulose (TEMPO-NCC) nanomaterials ( Fig. 4 C) ( Zaid et al, 2020 ). According to the results, this improved PNA biosensor showed a more extensive linear range (10 −13 -10 −8 M) and a lower detection limit (3.14 × 10 −14 M) than the previous study.…”
Section: Graphene Biosensors For Pathogensmentioning
confidence: 99%
“…Nowadays, various unmodified CNC/RGO hybrids were actively explored for different applications such as sensors, flexible electronics, supercapacitors and photonic devices [174]. Several approaches used to produce some unmodified CNC/RGO hybrids have been reported for which the common method used to produce CNC/GO can be applied.…”
Section: Cnc/rgomentioning
confidence: 99%